Integrated Transcriptomic and Metabolomic Analysis of Five Panax ginseng Cultivars Reveals the Dynamics of Ginsenoside Biosynthesis - Lee, Yun Sun; Park, Hyun-Seung; Lee, Dong-Kyu; Jayakodi, Murukarthick; Kim, Nam-Hoon; Koo, Hyun Jo; Lee, Sang-Choon; Kim, Yeon Jeong; Kwon, Sung Won; Yang, Tae-Jin (Frontiers in Plant Science, 2017)
Panax ginseng C.A. Meyer is a traditional medicinal herb that produces bioactive compounds such as ginsenosides. Here, we investigated the diversity of ginsenosides and related genes among five genetically fixed inbred ginseng cultivars (Chunpoong [CP], Cheongsun [CS], Gopoong [GO], Sunhyang [SH], and Sunun [SU]). To focus on the genetic diversity related to ginsenoside biosynthesis, we utilized in vitro cultured adventitious roots from the five cultivars grown under controlled environmental conditions. PCA loading plots based on secondary metabolite composition classified the five cultivars into three groups. We selected three cultivars (CS, SH, and SU) to represent the three groups and conducted further transcriptome and gas chromatography–mass spectrometry analyses to identify genes and intermediates corresponding to the variation in ginsenosides among cultivars. We quantified ginsenoside contents from the three cultivars. SH had more than 12 times the total ginsenoside content of CS, with especially large differences in the levels of panaxadiol-type ginsenosides. The expression levels of genes encoding squalene epoxidase (SQE) and dammarenediol synthase (DDS) were also significantly lower in CS than SH and SU, which is consistent with the low levels of ginsenoside produced in this cultivar. Methyl jasmonate (MeJA) treatment increased the levels of panaxadiol-type ginsenosides up to 4-, 13-, and 31-fold in SH, SU, and CS, respectively. MeJA treatment also greatly increased the quantity of major intermediates (and the expression of the underlying genes) in the ginsenoside biosynthesis pathway; these intermediates included squalene, 2,3-oxidosqualene, and dammarenediol II, especially in CS, which had the lowest ginsenoside content under normal culture conditions. We conclude that SQE and DDS are the most important genetic factors for ginsenoside biosynthesis with diversity among ginseng cultivars.